2020
DOI: 10.1002/aet2.10495
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Skills Training in Emergency Medicine Physicians Within the Edmonton Zone: A Needs Assessment

Abstract: Objectives: The objectives were to describe the current procedural skill practices, attitudes toward procedural skill competency, and the role for educational skills training sessions among emergency medicine (EM) physicians within a geographic health zone.Methods: This is a multicenter descriptive cross-sectional survey of all EM physicians working at 12 emergency departments (EDs) within the Edmonton Zone in 2019. Survey items addressed current procedural skill performance frequency; perceived importance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…11 Although it is unknown how many thoracenteses a physician should perform to be competent, studies have shown a positive association between the number of thoracenteses performed and the perceived competence, actual competence, and the complication rate. 1,[12][13][14] Importantly, it may be very difficult to achieve thoracentesis competencies using ad hoc bedside supervision without formalized training when the number of consultants being competent to perform thoracentesis is limited. Therefore, it is likely that a substantial amount of the Danish physicians in emergency medicine specialist training will have difficulties obtaining thoracentesis competencies given the current training efforts.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although it is unknown how many thoracenteses a physician should perform to be competent, studies have shown a positive association between the number of thoracenteses performed and the perceived competence, actual competence, and the complication rate. 1,[12][13][14] Importantly, it may be very difficult to achieve thoracentesis competencies using ad hoc bedside supervision without formalized training when the number of consultants being competent to perform thoracentesis is limited. Therefore, it is likely that a substantial amount of the Danish physicians in emergency medicine specialist training will have difficulties obtaining thoracentesis competencies given the current training efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have looked at the level of training, and/or frequency or quantity of performed procedures by the operator with procedural complications completed in the emergency room. One such study, conducted in Canada, surveyed Emergency Medicine physicians about procedural skills competency and found that confidence levels increased when more procedures were performed [ 11 ]. Further research is indicated to determine the best structure to utilize to maintain the procedural skills of veteran emergency medicine physicians, and how this system would be structured.…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, there is correlation between frequency of skill performance and perceived confidence at performing the skill. 4 While some EM education and training needs could be met through structured online video conferencing, procedural skills training was identified as a significant challenge. We sought to fill this gap by designing and conducting a real-time procedure-based hands-on workshop, facilitated remotely by a team of instructors, with the goal of giving the trainees an added opportunity to practice suturing under supervision of field experts.…”
Section: Objec Tive Of Innovationmentioning
confidence: 99%
“…Procedural skills, such as suturing, are an essential component of EM training 3 . Furthermore, there is correlation between frequency of skill performance and perceived confidence at performing the skill 4 . While some EM education and training needs could be met through structured online video conferencing, procedural skills training was identified as a significant challenge.…”
Section: Objective Of Innovationmentioning
confidence: 99%